The Effect of Hurdle Hopping and Burpees Exercises on Vertical Jump Ability in Volleyball Games of Extracurricular Students at SMPN 6 Palu - Vikkran Ruka; Christian Kungku; Didik Purwanto; Nyoman Sukrawan (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This study aims to determine the effect of hurdle hopping and burpees training on vertical jump ability in volleyball games of extracurricular students at SMPN 6 Palu. This study used an experimental method with a quantitative approach. The subjects of the study were students who participated in the volleyball extracurricular activities at SMPN 6 Palu. Data collection was carried out through vertical jump ability tests before and after being given a hurdle hopping and burpees training program. The data obtained were analyzed to determine the increase in vertical jump ability after being given the treatment. The results of the study are expected to show that hurdle hopping and burpees training can have a positive effect on increasing students' vertical jump ability. Hurdle hopping training can increase explosive power of leg muscles through repeated jumping movements, while burpees train strength, coordination, endurance, and explosive ability of the body. Thus, the application of both forms of training is expected to be an effective training method in improving students' vertical jump ability in volleyball games.